Multi‐causality and spatial non‐stationarity in the determinants of groundwater crustacean diversity in Europe. Issue 5 (20th October 2014) - Eme, David; Zagmajster, Maja; Fišer, Cene; Galassi, Diana; Marmonier, Pierre; Stoch, Fabio; Cornu, Jean‐Francois; Oberdorff, Thierry; Malard, Florian
<x xml:space="preserve">Abstract</x> The recognition of multi‐causality and spatial non‐stationarity in the determinants of large‐scale biodiversity patterns requires to consider the role of multiple mechanisms, their interactions, and how these mechanisms vary in strength relative to each other across geographical space. Here, we challenge the view that historical climate stability primarily drives European patterns of groundwater crustacean diversity by testing also the role of spatial heterogeneity and productive energy. First, we predicted that the three mechanisms would be equally important at continental scale when analyzed separately, but that the importance of historical climate variability would weaken in joint analyses due to co‐variation with the two other mechanisms. Second, we predicted that the three mechanisms would exhibit predictable latitudinal changes in their relative strength. To test these predictions, we selected predictors representing each mechanism and analyzed separately and jointly their effects and interactions using global regression models. We further mapped the independent and overlapping effects of mechanisms across Europe using partial geographically weighted regressions. When analyzed separately, the three mechanisms explained the same amount of variation in species richness, but in the joint analysis, the influence of historical climate stability became hidden in the variation shared with the other mechanisms. Topographic heterogeneity interacted synergistically with actual evapotranspiration and habitat heterogeneity on species richness. Spatial non‐stationarity in the independent and overlapping effects of the three mechanisms was the most plausible explanation for the hump‐shaped latitudinal pattern of crustacean species richness. Productive energy and spatial heterogeneity were important predictors at mid and southern latitudes, whereas historical climate stability overlapped with the two other mechanisms in northern Europe and productive energy in southern Europe. Multi‐causality and spatial non‐stationarity provide a broader perspective of groundwater biodiversity determinants that revives the importance of spatial heterogeneity and the strong dependence of subterranean communities on food supply from the surface.